SISTEM PENGUBURAN AKHIR JAMAN PRASEJARAH DI SULAWESI SELATAN - Akin Duli (Balai Arkeologi Provinsi Sulawesi Utara, 2018)
This paper described the forms of prehistoric burials in South Sulawesi. Results of this study indicate that there are different forms of burial has been known since the Neolithic period to ethnography period. Burial forms such as direct burial without the use of container, burial directly or indirectly by using containers. Vehicle used as a rock (stone coffin, gravel pit, stone carving), wood (erong, duni, allung, passilliran), ceramics (balubu, bowl, jar), or simply wrapped with a cloth or mat. Grave orientation is generally east-west or toward the sacred mountain, in accordance with their beliefs. Accompanied by a burial tomb various provisions, such as ceramics, objects of metal (gold, copper and bronze), beads and bracelets. Patterned pre-Islamic burial system is still life in certain communities, for example various forms tomb in Tana Toraja.